PENGARUH pH TERHADAP SINTESIS NANOPARTIKEL EMAS (AuNP s) DENGAN AGEN PENUDUNG ASAM GLUTAMAT - Ansyarif, Azmalaeni Rifkah; Sari, Desy Nurhasanah (Cokroaminoto Journal of Chemical Science, 2024)
Glutamic acid as a reducing and capping agent was used in the synthesis of gold nanoparticles (AuNPs). The effect of pH was investigated to determine the optimum conditions and formation of AuNPs. In this study, characterization was carried out using UV-Vis spectrophotomater. Based on the test results, it shows that glutamic acid can act as a reducer and a hood in the synthesis of AuNPs marked by a change in color from colorless to burgundy. The results showed that the optimum pH value in the formation of AuNPs was characterized by the highest absorbance intensity in the UV-Vis spectra. The maximal wavelength obtained was in the region of 530 nm and the highest absorbance intensity was obtained at pH 12.